Butamirate citrate associated methemoglobinemia - Chung-Chih Kao; Shu-Wei Hu; Hueng-Chuen Fan (Tungs’ Medical Journal, 2023)
Methemoglobinemia is a potentially life-threatening disease resulting from high blood levels of methemoglobin resulting in failure of binding and delivery of oxygen to tissues. The most common causes of methemoglobinemia are oxidizing toxins, such as butamirate citrate, which is a commonly used liquid antitussive, especially in pediatric patients. Herein, we present the case of a 3-year-old girl who accidentally ingested excessive amounts of butamirate citrate. She presented with mild lip cyanosis with high methemoglobin levels (6.5%) and normal oxygen saturation (98%), and was managed by prompt gut decontamination with activated charcoal, followed by monitoring and intravenous glucose administration. Therefore, methemoglobinemia should be considered a differential diagnosis in a patient presenting with cyanosis without any underlying lung or heart disease.